Case Report: Fever of unknown origin with hemophagocytic lymphohistiocytosis and intestinal hemorrhage—a successfully treated case of severe visceral leishmaniasis - Wang, Hongmei; Li, Jiajun; Huang, Wenxiang (Frontiers in Medicine, 2025)
In recent years, some cases of severe visceral leishmaniasis (VL) in immunocompetent adults have gradually been reported. Hemophagocytic lymphohistiocytosis (HLH) and intestinal hemorrhage are two rare complications in patients with VL. Without treatment, the mortality rate of such patients is extremely high. We report a case of a 31-year-old immunocompetent male who initially presented with fever of unknown origin (FUO), later developed HLH and experienced multiple episodes of life-threatening intestinal hemorrhage. The diagnosis of visceral leishmaniasis was confirmed through metagenomic next-generation sequencing (mNGS). The patient was successfully treated with amphotericin B deoxycholate (AmB-D) and supportive care. During the two-year follow-up period, no new complications were found. This case highlights the value of mNGS in the diagnosis of complex infectious diseases and emphasizes the clinical significance of the multidisciplinary collaborative model for patients with VL and complex complications. It can provide a reference for the early diagnosis and comprehensive treatment of severe VL.